A Prospective Observational Study on Assessment of Risk Factors, Complications and Clinical Efficacy of Hepatoprotectives and Antimicrobials in Treatment of Liver Diseases at Tertiary Care Teaching Hospital in Telangana - Sollu, Jaya; Pulusu, Mounika; Peddaramamolla, Deepthi; Islam, Jharna; Soma, Nikhil; Maram, Chinnaeswaraiah (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: The liver serves a variety of essential purposes, making it the most important organ. Chronic liver disease (CLD) has a wide range of etiologies, including toxins, alcoholism, infections, autoimmune illnesses, and hereditary problems. Patients are initially asymptomatic, as the disease progresses, signs like jaundice, icterus, pedal oedema, and abdominal distension can be seen. Liver functioning tests are used to assess liver disease progression. Liver disease may result in problems such as portal vein hypertension (PH). The treatment is to stop the disease and its associated complications from getting worse. For the treatment, a comprehensive strategy involving hepatoprotectives and antibacterial medications is required. Materials and Methods: This is a prospective observational study with the sample size of 200 patients. Patients were selected by simple random sampling. Then the patients were categorized according to their disease condition and collected data was analysed using suitable methods. Results: According to our research, chronic alcoholics have a higher risk of getting hepatitis and alcoholic fatty liver disease. The greatest treatment for liver disease is alcohol abstinence, which can be started as soon as possible. Avoiding alcohol will increase survival at all stages of the illness. Thiamine and ursodeoxycholic acid are the two hepatoprotectives that are most usually advised, followed by rifaximin and L-ornithine and L-aspartate (LOLA). Conclusion: Our research found that within the first week of treatment, serum bilirubin levels, aspartate transaminase levels, and alanine transaminase levels significantly decreased in people receiving hepatoprotective medications. The pharmacist is crucial for better therapeutic management based on the patient’s stage and condition.
Keywords: Risk factors; Complications; Alcoholic liver diseases; Hepatoprotectives; Antimicrobials